Birth setting, labour experience, and postpartum psychological distress. (July 2017) - MacKinnon, Anna L.; Yang, Lisa; Feeley, Nancy; Gold, Ian; Hayton, Barbara; Zelkowitz, Phyllis
Abstract: Objective: although psychosocial risk factors have been identified for postpartum depression (PPD) and perinatal posttraumatic stress disorder (PTSD), the role of labour- and birth-related factors remains unclear. The present investigation explored the impact of birth setting, subjective childbirth experience, and their interplay, on PPD and postpartum PTSD. Method: in this prospective longitudinal cohort study, three groups of women who had vaginal births at a tertiary care hospital, a birthing center, and those transferred from the birthing centre to the tertiary care hospital were compared. Participants were followed twice during pregnancy (12–14 and 32–34 weeks gestation) and twice after childbirth (1–3 and 7–9 weeks postpartum). Results: symptoms of PPD and PTSD did not significantly differ between birth groups; however, measures of subjective childbirth experience and obstetric factors did. Moderation analyses indicated a significant interaction between pain and birth group, such that higher ratings of pain among women who were transferred was associated with greater symptoms of postpartum PTSD. Conclusion and implications for practice: women who are transferred appear to have a unique experience that may put them at greater risk for postpartum psychological distress. It may be beneficial for care providers to help prepare women for pain management and potential unexpected complications, particularly if it is their first childbirth. Highlights: Symptoms of postpartum depression and PTSD did not differ across birth settings. Women report a more positive childbirth experience at the birthing centre. Women who are transferred report increased pain and a longer duration of labour. Among transferred women, higher pain predicts greater symptoms of postpartum PTSD.